Implementation of Narcotics Eradication Policy to Reduce Narcotics Circulation at Class IIA Tanjung Raja Correctional Facility - Raafi Hidayat; Prof Al Fitri; Abdul Najib; Raniasa Putra (Eduvest - Journal of Universal Studies, 2026)
This study aims to analyze the implementation of the narcotics eradication policy at the Tanjung Raja Class IIA Correctional Facility (Lembaga Pemasyarakatan Kelas IIA Tanjung Raja) and to identify the factors influencing the effectiveness of its rehabilitation program. A qualitative research design was employed, utilizing in-depth interviews with inmates and correctional officers, participant observation, and document analysis as data collection methods. The findings indicate that although positive steps have been undertaken such as the establishment of a dedicated task force and the implementation of a rehabilitation program the outcomes achieved have not been satisfactory. A reduction in narcotics circulation from 30% to 25% following one year of implementation does not reflect significant progress. Inhibiting factors, including budget constraints, human resource shortages, social stigma, and insufficient inter-agency coordination, contributed to weaknesses in policy implementation. These findings underscore the importance of improving rehabilitation facilities, providing capacity-building training for correctional officers, and strengthening collaboration among relevant agencies. Consequently, achieving effective narcotics eradication requires a more holistic and integrated approach involving all relevant stakeholders, including the government, the community, and the families of inmates. This study is expected to provide actionable recommendations for future policy improvement.